Peranan Universiti Awam Malaysia untuk melahirkan graduan kerja sosial sekolah - Sutharssan, Nadarajan (2018)
Social work is one of the areas of study that is increasingly gaining popularity among students pursuing higher education at university level. One of the specialisations in social work recognised by many countries is school social work. However, the school social work profession in Malaysia is yet to receive proper recognition. Thus, a study has been undertaken to explore the role of public universities in upholding school social work. Three major scopes of the study are current efforts, challenges and future planning of the universities in producing school social workers. This study utilises a qualitative method using semi-structured interviews. A total of 10 respondents were selected using purposive sampling among lecturers who have served for more than 10 years at selected public universities. All interviews were conducted based on the research questions. The findings show that current efforts undertaken by public universities include syllabus/courses, assignments, research, community programmes, and practicum. The challenges faced are the absence of the social work act and school social work post, the social work position that is not well-known by the public and the challenges faced by the universities in producing school social work graduates. Future planning of the universities discusses the teaching and learning aspects, practicum and course offerings. The respondents also raised up the issue of training school social work experts while receiving funds from the government, promoting studies and publication materials on school social work and educating the public about this field. Furthermore, the need to accelerate the social work act and promotion of school social workers and the role of the Malaysian Social Workers Association are also discussed. Therefore, collective actions should be taken by all relevant parties to overcome the challenges that exist and intensify the efforts of producing trained graduates in the field of school social work in Malaysia.